Evaluasi Geometri Jalan Angkut Batubara Menggunakan Hasil Pengukuran Terestrial Laser Scanner di PT Trubaindo Coal Mining Kabupaten Kutai Barat Provinsi Kalimantan Timur - Arya Lawing Sembiring; Windhu Nugroho; Ardhan Ismail; Henny Magdalena; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The evaluation of haul road geometry at PT Trubaindo Coal Mining was conducted to ensure that the haul road from the stockroom to the jetty meets applicable technical standards, thereby supporting the smoothness, safety, and efficiency of coal transportation activities. This study aims to analyze the conformity of haul road geometric parameters, including straight road width, curve width, curve radius, cross slope, longitudinal grade, and superelevation, based on the standards of AASHTO 7th Edition and Kepmen 1827 of 2018. The research method employed field measurements using a Terrestrial Laser Scanner (TLS), followed by data processing using Maptek and Surpac software. The obtained data were then compared with the applicable standards to determine the level of conformity of the haul road geometry. Based on field measurements, the average values obtained were 14.99 m for straight road width, 18.45 m for curve width, 0.22 m for cross slope, 6.97% for grade, 223.51 m for curve radius, and 1.40 m for superelevation. Furthermore, based on calculations and analysis referring to AASHTO 7th Edition and Kepmen 1827 of 2018, and considering the largest haulage equipment used (Volvo FMX 480), the ideal haul road geometry values were determined as follows: 13 m for straight road width, 17 m for curve width, 124 m for curve radius, 0.26 m for cross slope, 1 m for superelevation, and 6% for grade based on PT Trubaindo Coal Mining standards.